Validation of the Catherine Bergego Scale in patients with unilateral spatial neglect after stroke - Marques, Carlos Leonardo Sacomani [UNESP]; Souza, Juli Thomaz de [UNESP]; Gonçalves, Maicon Gabriel [UNESP]; Da Silva, Taís Regina [UNESP]; Da Costa, Rafael Dalle Molle [UNESP]; Modolo, Gabriel Pinheiro [UNESP]; Corrente, José Eduardo [UNESP]; Bazan, Rodrigo [UNESP]; Luvizutto, Gustavo José (FapUNIFESP (SciELO), 2019)
The Catherine Bergego Scale (CBS) is a scale to evaluates the impact of unilateral spatial neglect (USN) on everyday life of patients after stroke. Objective: The aim of this study was to evaluate the reliability and comprehension of the Portuguese version of the CBS for patients with USN after stroke. Methods: This was a cross-sectional study in patients with stroke and USN. The CBS was translated, culturally adapted and applied by two independent investigators. The patients were also evaluated by the Behavioural Inattention Test (BIT), NIHSS, mRS and Barthel scale to assess USN severity, neurological function, disability and autonomy consecutively. Consistency and coherence were analysed using Cronbach’s α, inter-observer reliability by Kappa, and the correlation between the CBS, BIT, NIHSS, mRS, and Barthel was determined using Pearson correlation. Results: Twenty-two patients were evaluated and the observed Cronbach’s α=0.913. For intra-observer reproducibility, the 10 items showed a reasonable and high reliability between evaluators. The CBS showed a negative correlation with the BIT. There was a low correlation between the BIT and NIHSS, mRS and Barthel index. Conclusion: The CBS is an adequate and validated scale for assessing patients with USN after stroke in a Brazilian population.
Validação da escala catherine bergego em pacientes com negligência espacial unilateral após acidente vascular cerebral
Keywords: Catherine bergego scale; Portuguese; Scale; Unilateral spatial neglect; Validation